Phyllodes tumour with heterologous sarcomatous differentiation: Case series with literature review. (2015) - Warrier, Sanjay; Hwang, Sang Y.; Gibbings, Keagan; Carmalt, Hugh; O'Toole, Sandra
Highlights: Phyllodes tumours with heterologous sarcomatous differentiation are extremely rare. We report 2 such cases in females in their fifties and describe the clinical presentation, diagnostic investigations and management with 2 year follow-up. There is limited literature to guide adjuvant therapy and prognosis of phyllodes tumours with heterologous sarcomatous differentiation. Abstract: Introduction: Phyllodes tumours are rare fibroepithelial malignancies of the breast, accounting for less than 1% of malignant breast tumours. Further malignant differentiation of phyllodes tumours can occur, resulting in cases of extremely rare heterologous sarcomatous differentiation. Presentation of case: Two females in their fifties were diagnosed with malignant phyllodes tumour associated with heterologous sarcomatous differentiation. The first patient, aged 50 had phyllodes tumour with chondrosarcoma, osteosarcoma and ductal carcinoma-in-situ. The second patient, aged 53 had phyllodes tumour with osteosarcoma and liposarcoma. Discussion: The association of phyllodes tumour and heterologous sarcomatous differentiation is rare, with only 4 previously reported cases in English literature. The paucity of evidence presents challenges in its management with uncertain prognosis and monitoring requirements for two aforementioned patients. Conclusion: Further case series and long-term follow up is required for accurate characterisation of phyllodes tumours with heterologous sarcomatous differentiation.